Baroreflex sensitivity predicts therapeutic effects of metoprolol on pediatric postural orthostatic tachycardia syndrome - Cui, Yaxi; Wang, Yuanyuan; Liu, Ping; Wang, Yuli; Du, Junbao; Jin, Hongfang (Frontiers in Cardiovascular Medicine, 2022)
Objective: To determine if the baseline baroreflex sensitivity (BRS) could be a useful predictor for the metoprolol therapeutic efficacy on postural orthostatic tachycardia syndrome (POTS) in children. Methods: In this retrospective case-control study, fifty-four children suffering from POTS treated with metoprolol were recruited from the pediatric department of Peking University First Hospital. After 2-3 months of metoprolol treatment, all subjects were divided into responders and non-responders based on whether the symptom score (SS) was decreased by over 50% after metoprolol treatment at the follow-up. The baseline demographic parameters and the supine BRS during head-up tilt test (HUTT) obtained by Finapres Medical System-FMS were compared between the two groups. The value of BRS to predict the effectiveness of POTS was analyzed by a receiver-operating characteristic (ROC) curve. Results: The age, sex, height, weight, body mass index (BMI), course of the disease, baseline SS, mean length of treatment, and metoprolol dose of the subjects were not statistically different between the responders and non-responders (P > 0.05). The decline of symptom scores (ΔSS) of the responders was more obvious than that of the non-responders (P < 0.01). The supine BRS, BRS at max HR, supine heart rate (HR) and max HR were different between responders and non-responders (P < 0.01, P < 0.05, P < 0.01, P = 0.047). The binary multivariable analysis showed that baseline supine BRS was significantly associated with the response to metoprolol therapy (OR: 2.079, 95% CI: [1.077, 4.015], P = 0.029). According to the ROC curve, the area under the curve (AUC) of baseline BRS was 0.912 (95 %CI, 0.840-0.984), with a cutoff value of 8.045 ms/mmHg, yielding a sensitivity and specificity of 75.8% and 95.2%, respectively, in predicting the effectiveness of POTS. Conclusion: The baseline BRS level > 8.045 ms/mmHg can predict a good therapeutic response to metoprolol and the results would assist in guiding the individualized - adrenoceptor blocker use in pediatric patients suffering from POTS.